KAJIAN SOSIAL EKONOMI PENDUDUK USIA LANSIA DI KOTA PONTIANAK - WICAKSONO B21107022, ARIES NUR (Jurnal Curvanomic, 2014)
This research is aimed to describe about the elderly socioeconomic and also to study about the ageing level of welfare in accordance with the ageing right. The elderly population is the part of family and part of public which are increasing in number in line with the increasing of life expectancy. The number increasing of ageing will impact toward the socioeconomic within the family, society, or in government.Â  Economic implication which is important from the increasing of population is the increasing in ageing dependence ratio. This research is using the qualitative approach and the descriptive research method. Collecting data technique is using the structured interviews (questioners) and observing. By the purposive sampling technique, this research researched a number of elderly in 6 (six) sub-districts in Pontianak City. The result of this research shown the Ageing population characteristic in Pontianak City is dominated by women they are 51%, meanwhile the age of the most respondents are between 60 to 65 years old (41%), 64% of respondents are married, the most of respondents are Malayness which is 30%, 85% respondents are Moslem and the average of respondent are graduated from Elementary School. About 54% respondents are still working. Whereas, the average of respondents income is about Rp. 1.000.000,00 â€“ Rp. 2.000.000,00, their job is dominated with entrepreneurship for 57,40% by the working time average is 5-6 hours / day and average of them have 1-2 life burden. 23,11% respondents are suffering aches for three months last.